Notary Authority in Providing Legal Consultation Outside Of Notary Deeds: In Compliance With The Code of Ethics and Social Responsibility of Notaries - Calvin, Calvin; Sinaga, Henry; Siregar, Mahmul (Jurnal Hukum Replik, 2025)
This research examines the role of notaries in providing legal counseling and legal consultation as a manifestation of the social responsibility of the legal profession. Using normative juridical research methods with descriptive analytical approaches that rely on secondary data and literature study techniques, this research finds that notaries have a strategic role in creating legal awareness in society through legal counseling that is collective, preventive, and educative, as well as legal consultation that is individual and curative. However, the research results show that there is normative ambiguity regarding notaries' authority in providing legal consultation, where formally notaries are only authorized to provide legal counseling in the context of deed preparation, but in practice they often provide legal consultation free of charge as a form of social responsibility. This research concludes that clearer and more definitive regulations are needed to provide legal certainty regarding the limits of notaries' authority in providing legal consultation, so as to strengthen the position of notaries as public servants in the field of law without violating professional ethics.Keywords: Notary, legal consultation, notarial deed.